Pengantar Hukum Pajak Serta Aturan dan Regulasi yang Berlaku - Annisa Afwani; Nidaul Husna; Muhammad Saladin Zidan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Tax law is a branch of public law that governs the relationship between the state and taxpayers in terms of tax collection. In the context of modern taxation systems, tax law not only encompasses the legal basis for tax imposition but also includes the set of rules and regulations that underpin its implementation and enforcement. This article aims to provide a comprehensive understanding of the concept of tax law, the fundamental principles of taxation, the types of taxes according to legislation, and the development of tax regulations currently enforced in Indonesia. Using a normative approach, this article analyzes the legal foundations of taxation such as the General Provisions and Tax Procedures Law (UU KUP), as well as supporting legislation including the Law on Harmonization of Tax Regulations (UU HPP). The discussion also covers the principle of fairness in taxation, the authority of the Directorate General of Taxes, and the rights and obligations of taxpayers. With a robust legal framework and continuously updated regulations, the tax system is expected to provide legal certainty, improve compliance, and create a fair and sustainable system.